Antibacterial Titanium Implants Biofunctionalized by Plasma Electrolytic Oxidation with Silver, Zinc, and Copper: A Systematic Review - van Hengel, Ingmar A. J. (Int J Mol Sci, 2021)
Patients receiving orthopedic implants are at risk of implant-associated infections (IAI). A growing number of antibiotic-resistant bacteria threaten to hamper the treatment of IAI. The focus has, therefore, shifted towards the development of implants with intrinsic antibacterial activity to prevent the occurrence of infection. The use of Ag, Cu, and Zn has gained momentum as these elements display strong antibacterial behavior and target a wide spectrum of bacteria. In order to incorporate these elements into the surface of titanium-based bone implants, plasma electrolytic oxidation (PEO) has been widely investigated as a single-step process that can biofunctionalize these (highly porous) implant surfaces. Here, we present a systematic review of the studies published between 2009 until 2020 on the biomaterial properties, antibacterial behavior, and biocompatibility of titanium implants biofunctionalized by PEO using Ag, Cu, and Zn. We observed that 100% of surfaces bearing Ag (Ag-surfaces), 93% of surfaces bearing Cu (Cu-surfaces), 73% of surfaces bearing Zn (Zn-surfaces), and 100% of surfaces combining Ag, Cu, and Zn resulted in a significant (i.e., >50%) reduction of bacterial load, while 13% of Ag-surfaces, 10% of Cu-surfaces, and none of Zn or combined Ag, Cu, and Zn surfaces reported cytotoxicity against osteoblasts, stem cells, and immune cells. A majority of the studies investigated the antibacterial activity against S. aureus. Important areas for future research include the biofunctionalization of additively manufactured porous implants and surfaces combining Ag, Cu, and Zn. Furthermore, the antibacterial activity of such implants should be determined in assays focused on prevention, rather than the treatment of IAIs. These implants should be tested using appropriate in vivo bone infection models capable of assessing whether titanium implants biofunctionalized by PEO with Ag, Cu, and Zn can contribute to protect patients against IAI.